(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In all developed countries, the need for qualified nurses is high. The main task of medicine is to preserve human health, prevent diseases, prolong human life, and rehabilitate. Our main assistants in maintaining health are nurses. The main link in the activities of multidisciplinary nurses is the organization of primary health care. Promoting a healthy lifestyle - teaching healthcare, providing first aid, conducting medical procedures, caring for bedridden patients - in general, nurses are the main protectors of patients. Promoting a healthy lifestyle begins with the family. A family nurse implementing a healthy lifestyle support program should be able to assess the family as a system, identify its cultural and ethnic characteristics, diet, harmful habits and risk factors, and the health of the family and its members.